Equation of State for Water in the Small Compressibility Region - Bardik, V.Yu.; Nerukh, D.; Pavlov, E.V.; Zhyganiuk, I.V. (Ukrainian Journal of Physics, 2012)
The equation of state for dense fluids has been derived within the framework of the Sutherland and Katz potential models. The equation quantitatively agrees with experimental data on the isothermal compression of water under extrapolation into the high pressure region. It establishes an explicit relationship between the thermodynamic experimental data and the effective parameters of the molecular potential.